Optimization of TDZ Hormone on the Formation of Somatic Embryogenesis in Dendrobium Orchids (D.50TH Stage Beauty X D. Bobby Mesina) - Didik Pudji Restanto; Iqbal Felayati; Wahyu Indra Duwi Fanata; Parawita Dewanti; Budi Kriswanto; Mohammad Nur Khozin; Mohammad Candra Prayoga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2023)
The Dendrobium variety orchid is a plant that has rare potential and growth. This requires large amounts of seeds that can be propagated in vitro. This study aims to determine the effect of TDZ on the direct induction of somatic embryogenesis. The study was conducted using a completely randomized design (CRD) with one factor, namely media consisting of basal Murashige and Skoog (MS) media with growth regulator TDZ. Each treatment out of a total of seven treatments was repeated four times. The research was carried out from March 2022 to August 2022. The results showed that leaf explants (clonal) could only be induced in 2 treatments (1 mg/L and 1.5 mg/L) out of 28 experimental media treatment units. The earliest callus appeared in the 1 mg/L treatment with a growth time of 90 days after planting (DAP) and the earliest PLB appeared in the 1.5 mg/L treatment with a growing time of 45 days after planting (DAP), the percentage of explant growth that became PLB with 1.5 mg/L treatment resulted in a percentage of 20 % and the percentage of callus growth at 1 mg/L yields a percentage of 20%.